Typhus in Buchenwald: Can the Story Be Told? - Löwy, Ilana (ETHICS IN PROGRESS, 2020)
Ludwik Fleck is known today primarily as pioneer in the social study of scientific knowledge. However, during World War II he was a prisoner in Buchenwald, where he and other prisoners produced a typhus vaccine for the Nazis, and where he witnessed murderous experiments on human beings. After WW2, Fleck was accused by one of the prisoners who had participated in the vaccine production at Buchenwald of collaborating, either deliberately or due to lack of imagination, with the Nazi experiments. This article critically examines this accusation and its well-documented rebuttal by Fleck. It argues that while sometimes, especially when dealing with emotionally fraught issues, it may be difficult to establish what precisely took place at a given time and site, it is important to restore the original complexity and messiness of past events – in order to open spaces for understanding, reflexivity and compassion.